Legends of drag : queens of a certain age - Hanson, Harry James; Antheus, Devin (Cernunnos, an imprint of Abrams, 2022)
"Drag has officially transcended the underground and exploded into the mainstream. Queens have more visibility than ever, and it's been hard won through decades of perseverance, imagination, and intergenerational support within local drag scenes. It's time to honor the queens who paved the way for the new generation and are still carrying out their work today. To create Legends of Drag, a photo book and archive of living queer history, authors Harry James Hanson and Devin Antheus traveled coast to coast, visiting 16 cities to meet 80 legendary entertainers who shared boundless wisdom and powerful anecdotes from their lives"--